Infographics as a visual communication tool in sports: The representation of the Indonesian national team on Okezone.com in June 2025 - Masyhudi, Imamul; Prasetyo, Martinus Eko (Deskomvis: Jurnal Ilmiah Desain Komunikasi Visual, Seni Rupa dan Media, 2025)
Infographics have become one of the most important journalistic products in online media, especially for young readers who prefer visually rich and concise content. However, infographics are still often perceived merely as tools for presenting data, whereas they contain narratives, visual choices, and symbolism that can influence public emotions and perceptions. The urgency of this research arises from the fact that infographics depicting national representation often shape public perception subtly yet significantly. This study aims to analyze the role of infographics in sports journalism, focusing on infographics published by Okezone.com about the Indonesian National Team (Timnas Indonesia). Timnas holds a privileged position as a national symbol of pride, making its representation in infographics particularly important. The study employs visual content analysis with a descriptive qualitative approach, using seven infographics about Timnas Indonesia published in June 2025. The findings show that infographics do not merely present data and visuals; they also construct narratives and produce meanings for the public. Elements such as the red-white color palette, the Garuda emblem, player photographs, and statistical figures are combined to build the image of the national team. In both pre-match contexts and post-match reporting, the visuals convey optimism and heroism. These findings affirm that infographics play a crucial role in shaping perception and strengthening national identity on the international stage, while also contributing to visual journalism studies and editorial practices in producing more responsible and meaningful visual content.